Perceived Stress in Older Dementia Caregivers: Mediation by Loneliness and Depression. (3rd January 2022) - Peavy, Guerry; Mayo, Ann M.; Avalos, Cynthia; Rodriguez, Amanda; Shifflett, Benjamin; Edland, Steven D.
Coupled with aging, chronic stress experienced by dementia caregivers often leads to deteriorating health. Comparing caregivers and non-caregivers, we tested whether depression and loneliness mediate the relationship between caregiver status and a measure of chronic stress, the Perceived Stress Scale. Seventy-six cognitively normal older adults (mean age 72.7) were identified as caregivers or non-caregivers based on the functional independence of a paired family member. Caregivers reported more perceived stress, depression, and loneliness than non-caregivers. Using multiple mediation analyses, we found that loneliness and depression mediated the relationship of caregiver status with perceived stress. The loneliness effect on perceived stress was both direct and via its relationship with depressive symptoms. The findings suggest loneliness as a likely point of intervention to reduce caregiver stress. Initiatives to enable caregivers to maintain or develop social relationships apart from caregiver responsibilities may mitigate stress and its negative impact on mental and physical health.